Central Nervous System Fungal Infection and Acute Lymphoblastic Leukemia in Children: What is the Optimal Duration of Antifungal Therapy?. Issue 6 (August 2017) - Lashkari, Harsha P.; Fernandes, Neil; Alva, Kishan; Rai, Santosh
Abstract : Invasive fungal infections are rare in children with acute lymphoblastic leukemia. It compromises the antileukemia therapy should it happen. Central nervous system fungal infections carry high mortality. We here report the case of a 6.5-year-old girl who developed multiple central nervous system fungal abscesses possibly due to Aspergillus infection during induction therapy for acute lymphoblastic leukemia who has been successfully managed without compromising antileukemia therapy. She has been receiving antifungal therapy and maintenance chemotherapy for 20 months from diagnosis. We reviewed literature about the optimal duration of therapy for such children as the reported cases duration ranged between 4 and 24 months.